Stock Prices in Food and Beverage Companies Before and After the Pandemic - Hendri Maulana; Annisa Fitri Anggraeni; Jaja; Mochamad Zakaria; Poniah Juliawati; Anna Noviana; Nandan Limakrisna (DINASTI RESEARCH, 2023)
Investment is a commitment to a number of funds or other resources that are currently being carried out with the aim of obtaining profits in the future or can be interpreted as investing money in a company or project for the purpose of obtaining profits. Basically investing is buying an asset that is expected to be resold in the future at a higher value. The expectation of future profits is a compensation for the time and risk associated with an investment made. There are various types of investments on the market, including; time deposits, Bank Indonesia Certificates, stocks, bonds, money market securities, derivative products, property, gold, mutual funds, foreign currencies. The population is food and beverage companies that are listed on the Indonesia Stock Exchange and have closing stock price data, and the sample is 9 food and beverage company on the period 2017-2019 using data panel regression with e-views. The results showed that earnings per share (EPS) had a positive and significant effect on stock prices. Then, Return on Assets (ROA) has a positive and significant effect on stock prices. Also, Debt to Equity Ratio (DER) has a negative and insignificant effect on stock prices.